PERAN SEKRETARIAT DPRD KABUPATEN NIAS BARAT DALAM PENINGKATAN KINERJA DPRD KABUPATEN NIAS BARAT - Panjaitan, Doli Tua Mulia Raja; Waruwu, Passejahtera (JURNAL PROINTEGRITA, 2020)
The support of the West Nias Regency DPRD (Regional People's Representative Assembly) secretariat is urgently needed so that the DPRD's performance can run well in order to absorb and carry out the aspirations of the people of West Nias Regency to carry out the Legislation, Budget and oversight functions. This study aims at: (i) finding the role of the West Nias Regency DPRD Secretariat in enhancing the performance of the West Nias Regency DPRD (ii) analyzing the factors that support and hinder the West Nias Regency DPRD Secretariat to improve the performance of the West Nias Regency DPRD. This research is descriptive with a qualitative approach. Research informants: key informants: West Nias DPRD Secretariat and key informants: DPRD members West Nias Regency. Data analysis technique used by the qualitative method Results: the role of the West Nias Regency DPRD Secretariat in the Improvement of the West Nias Regency DPRD shows 82% or between 80% to 100% good performance. Supporting factors are: optimization of available budget, cooperation and solid teamwork, maximizing facilities and infrastructure facilities. Inhibiting factors are lack of coordination and division of tasks is not optimal and scheduling of activities that almost coincides with implementation time especially in the procurement of facilities and infrastructure that supports the smooth administration of offices as well as several other activities in the capacity building program for regional people's representative institutions and limited staff of the DPRD Secretariat